Serological identification of rodent strains of Actinomyces viscosus and their relationship to Actinomyces of human origin - Bellack, S.; Jordan, H.V. (Archives of oral biology, 1972)
Strains of Actinomyces viscosus of rat and hamster origin, known to be morphologically and biochemically similar, appeared identical when compared by agglutination reactions, fluorescent antibody staining, and gel diffusion. Reference strains of known Actinomyces species were easily differentiated from the rodent strains. In a sampling of 65 Actinomyces isolates from human dental plaque, 32 strains showed varying degrees at agglutination of comparatively low titres below 1:800, when tested against high titre antiserum to the hamster-type strain. Ten strains agglutinated spontaneously and 23 strains showed no agglutination. Fluorescent-tagged gamma globulin fractions of high titre antiserum provided a specific means of differentiating the rodent serotype of A. viscosus from known Actinomyces species and from 65 randomly isolated strains of human origin. Direct microscopic examination of dental plaque material from 24 subjects failed to detect any cells that reacted at significant titre with fluorescent tagged antiserum specific for the rodent serotype of A. viscosus. Des espèces d' A. viscosus de rat et de hamster, identiques morphologiquement et biochimiquement, semblent similaires au point de vue des réactions d'agglutination, de la coloration par fluorescence des anticorps et par diffusion de gel. Des souches de référence de divers Actinomyces connus sont facilement différenciées des espèces provenant des rongeurs. Sur 65 Actinomyces, isolés dans une plaque dentaire humaine, 32 souches présentent divers degrés d'agglutination à des dilutions comparativement basses en dessous de 1:800, lorsqu'on les teste avec un antiserum à concentration élevée contre la souche de hamster. Dix souches s'agglutinent spontanément et 23 espèces ne présentent pas d'agglutination. Des fractions de gamma globulines fluorescentes d'antiserum à concentration élevée, permettent de différencier spécifiquement le sérotype de rongeur d' A. viscosus d'espèces connues et de 65 espèces humaines, recueillies au hasard. L'examen microscopique direct de plaques de 24 sujets ne permet pas de mettre en évidence des cellules qui réagissent à une dilution significative avec un antisérum fluorescent, spécifique pour le sérotype de rongeur d' A. viscosus. Morphologisch und biochemisch einander ähnliche A. viscosus-Stämme von Ratten und Hamstern erschienen identisch, wenn sie durch Agglutinationsreaktionen, Fluorescenz-Antikörperfärbung und Geldiffusion verglichen wurden. Vergleichsstämme bekannter Actinomyces-Arten lieβen sich leicht von den Nagerstämmen unterscheiden. Unter 65 Actinomyces-Isolaten aus menschlichen Zahnplaques zeigten 32 Stämme unterschiedliche Grade der Agglutination und vergleichsweise niedrige Titer unter 1:800, wenn sie gegen das für den Hamsterstamm spezifische Hochtiterantiserum geprüft wurden. 10 Stämme agglutinierten spontan und 23 zeigten keine Agglutination. Fluoreszierende Gammaglobulinfraktionen des Hochtiterantiserums bildeten ein spezifisches Hilfsmittel zur Unterscheidung zwischen dem Nager-Serotyp von A. Viscosus und den bekannten Actinomycesarten wie auch den 65 zufällig isolierten Stämmen menschlicher Herkunft. Die direkte mikroskopische Betrachtung des Plaquematerials von 24 Personen ergab keinerlei Zellen, die in bemerkenswertem Ausmaβ mit dem für den Nager-Serotyp von A. viscosus spezifischen fluoreszierenden Antiserum reagierten.